Assembly and Analysis of the Mitochondrial Genome of Hippophae rhamnoides subsp. sinensis, an Important Ecological and Economic Forest Tree Species in China - Jie Li; Song-Song Lu; Yang Bi; Yu-Mei Jiang; Li-Dan Feng; Jing He (Plants)
Hippophae rhamnoides subsp. sinensis is extensively found in China, where the annual precipitation ranges from 400 to 800 mm. It is the most dominant species in natural sea buckthorn forests and the primary cultivar for artificial ecological plantations. Additionally, it exhibits significant nutritional and medicinal value, making it a renowned eco-economic tree species. Despite extensive research into its ecological functions and health benefits, the mitochondrial genome of this widespread species has not yet been published, and knowledge of the mitochondrial genome is crucial for understanding plant environmental adaptation, evolution, and maternal inheritance. Therefore, the complete mitochondrial genome was successfully assembled by aligning third-generation sequencing data to the reference genome sequence using the Illumina NovaSeq 6000 platform and Nanopore Prometh ION technologies. Additionally, the gene structure, composition, repeat sequences, codon usage bias, homologous fragments, and phylogeny-related indicators were also analyzed. The results showed that the length of the mitochondrial genome is 454,489 bp, containing 30 tRNA genes, three rRNA genes, 40 PCGs, and two pseudogenes. A total of 411 C-to-U RNA editing sites were identified in 33 protein-coding genes (PCGs), with higher frequencies observed in ccmFn, ccmB, nad5, ccmC, nad2, and nad7 genes. Moreover, 31 chloroplast-derived fragments were detected, accounting for 11.86% of the mitochondrial genome length. The ccmB, nad4L, and nad7 genes related to energy metabolism exhibited positive selection pressure. The mitochondrial genome sequence similarity between H. rhamnoides subsp. sinensis and H. tibetana or H. salicifolia was 99.34% and 99.40%, respectively. Fifteen shared gene clusters were identified between H. rhamnoides subsp. sinensis and H. tibetana. Phylogenetically, the Rosales order showed close relationships with Fagales, Fabales, Malpighiales, and Celastrales. These findings provide fundamental data for exploring the widespread distribution of H. rhamnoides subsp. sinensis and offer theoretical support for understanding the evolutionary mechanisms within the Hippophae genus and the selection of molecular breeding targets.